If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -8) + -1(8x + 7) = 0 Reorder the terms: (-8 + 6x) + -1(8x + 7) = 0 Remove parenthesis around (-8 + 6x) -8 + 6x + -1(8x + 7) = 0 Reorder the terms: -8 + 6x + -1(7 + 8x) = 0 -8 + 6x + (7 * -1 + 8x * -1) = 0 -8 + 6x + (-7 + -8x) = 0 Reorder the terms: -8 + -7 + 6x + -8x = 0 Combine like terms: -8 + -7 = -15 -15 + 6x + -8x = 0 Combine like terms: 6x + -8x = -2x -15 + -2x = 0 Solving -15 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -2x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -2x = 0 + 15 -2x = 0 + 15 Combine like terms: 0 + 15 = 15 -2x = 15 Divide each side by '-2'. x = -7.5 Simplifying x = -7.5
| 2x(3x-9)+2= | | 1v/321v=2 | | 7x+3y=3x+5y | | -3(s+2)=0 | | -2(r+-1)=0 | | 41=19-2a | | b+30+2b= | | 5/8k=21/2 | | 50=16p+2 | | 8x-3=4x-21 | | 9a^2-18a+1=-4 | | 10=2(s+12) | | (3w^2-1)*w=96 | | (5/6)*x=10 | | W^2-2w=24+3w | | x^2-13=32 | | 24+9b=-3 | | 15-14=L | | 2(h+1)=10 | | 3(-8q+5)=4(q+1) | | -4+4x=-3x+24 | | 2n+9=33 | | 2(m+2)=8 | | -35=y-4 | | X+3=10-2X | | 1/2n-1/3=1 | | 2x+4y-9=0 | | F(X)=10X^2+27X-28 | | 10/3x=34/5 | | (X+2)(x-3)=2x(x-4) | | 4r^2-22r-42=0 | | 2X=3X-5+2X+12 |